Factors Associated With General Surgery Residents’ Operative Experience During the COVID-19 Pandemic - Purdy, Amanda C. (JAMA Surg, 2021)
IMPORTANCE: The suspension of elective operations in March 2020 to prepare for the COVID-19 surge posed significant challenges to resident education. To mitigate the potential negative effects of COVID-19 on surgical education, it is important to quantify how the pandemic influenced resident operative volume. OBJECTIVE: To examine the association of the pandemic with general surgical residents’ operative experience by postgraduate year (PGY) and case type and to evaluate if certain institutional characteristics were associated with a greater decline in surgical volume. DESIGN, SETTING, AND PARTICIPANTS: This retrospective review included residents’ operative logs from 3 consecutive academic years (2017-2018, 2018-2019, and 2019-2020) from 16 general surgery programs. Data collected included total major cases, case type, and PGY. Faculty completed a survey about program demographics and COVID-19 response. Data on race were not collected. Operative volumes from March to June 2020 were compared with the same period during 2018 and 2019. Data were analyzed using Kruskal-Wallis test adjusted for within-program correlations. MAIN OUTCOME AND MEASURES: Total major cases performed by each resident during the first 4 months of the pandemic. RESULTS: A total of 1368 case logs were analyzed. There was a 33.5% reduction in total major cases performed in March to June 2020 compared with 2018 and 2019 (45.0 [95% CI, 36.1-53.9] vs 67.7 [95% CI, 62.0-72.2]; P < .001), which significantly affected every PGY. All case types were significantly reduced in 2020 except liver, pancreas, small intestine, and trauma cases. There was a 10.2% reduction in operative volume during the 2019-2020 academic year compared with the 2 previous years (192.3 [95% CI, 178.5-206.1] vs 213.8 [95% CI, 203.6-223.9]; P < .001). Level 1 trauma centers (49.5 vs 68.5; 27.7%) had a significantly lower reduction in case volume than non–level 1 trauma centers (33.9 vs 63.0; 46%) (P = .03). CONCLUSIONS AND RELEVANCE: In this study of operative logs of general surgery residents in 16 US programs from 2017 to 2020, the first 4 months of the COVID-19 pandemic was associated with a significant reduction in operative experience, which affected every PGY and most case types. Level 1 trauma centers were less affected than non–level 1 centers. If this trend continues, the effect on surgical training may be even more detrimental.